Exploring the conflict management process: a case study of the department of labor in Malaysia / Sabiroh Md Sabri, S. K. Musairah and Nurul Diyana Jelani - Md Sabri, Sabiroh; Musairah, S. K.; Jelani, Nurul Diyana (Universiti Teknologi MARA, Perlis, 2021)
Conflict is a phenomenon of negative emotional feelings and reactions that arise between parties with different opinions, ideas and views. Conflict in an organization is almost unavoidable. Conflict might happen between an employer and an employee when there is dissatisfaction or disagreement between them towards certain work situation. The employee sometimes does not have a mutual understanding with his employer regarding certain issue until the end. This will lead to the involvement of a third party to help them resolve the problem. In Malaysia, the Labor Department is responsible for managing conflict between an employee and his employer. To ensure that the conflict is being handled effectively and efficiently, it is crucial for the Labor Department to have a set of strategies to help them in the conflict management process. However, our preliminary investigation shows that no standard or specific work process is being used by the department. Every officer used their method in managing the conflict assigned to them. Thus, it caused the department not being efficient in handling the cases. To address this issue, this study explores the process of conflict management carried out and proposed a standard procedure of conflict management that can be used by the Labor Department. This research adopted the qualitative method using a case study approach and aimed to understand the elements involved in the process of conflict management. Data was collected using semi-structured interviews involving five respondents consists of officers in the department. The results of this research have identified nine elements in the conflict management process. Results from this research could be used by the Labor Department in strategizing their method of managing conflict handled by the department. By having a standardized method, officers could handle the task more smoothly, thus increase the efficiency of the department and customer satisfaction and help the department to continue to be competitive and able to serve their customer better in the future.